KARAKTER VISUAL KAWASAN WISATA BATIK TULIS LASEM KABUPATEN REMBANG - Mutiawati Mandaka; Adi Sasmito; Taufiq Rizza Nuzuluddin (Universitas Muhammadiyah Semarang, 2018)
Research on Visual Character of Lasem Batik Tulis Tourism Area Rembang Regency aims to look for components that shape and influence the visual character of the Lasem Batik Tulis tourist area and to find a visual link between the visual characters of some Batik Tulis Lasem areas in the Lasem Batik Tourism Area of Rembang Regency. There are several things that are studied to see the visual character of the area, namely the physical character component of architecture which includes: Building Character: Building facade, building height scale, style / style, material, texture, color; Environmental Character: path, edge, node, landmark. And then to see the visual character of the area also need to study the non-physical character behind the physical formation. Based on the results of the research and discussion that has been carried out, it can be concluded that the visual character of this Batik Tulis tourism village is formed from physical character as the main component and is supported by the presence of non-physical characters as a supporting component, taking into account the history of Lasem development. In Babagan Village, the character of the surviving dwelling house is an original character that is a regional identity so it is important to find the type of visual character so that it can be determined how to maintain it and can provide input as a consideration for aspects or components that need to be maintained and components that must be developed in the area revitalization Tourism Village of Rembang Regency. Keyword: Visual character, Lasem Batik Tulis Tourism Area Rembang Regency